ANALISIS KESALAHAN SISWA KELAS X SMK DALAM MEMAHAMI KONSEP DASAR BENTUK EKSPONEN - Rizki Anugrah Supriyatno; M. Ardi; Ita Septiyanih; Frida Asria Hediana; Marcella Galuh Prabaningtyas; Kamelia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the errors made by Grade X students at SMK PGRI 23 Jakarta in understanding the basic concepts of exponential forms and to identify the factors contributing to these errors. A descriptive qualitative approach was employed. Data were collected through written tests and analyzed based on the types of errors appearing in the students' work. The results indicate that the most frequent errors involved understanding the meaning of exponentiation, applying properties of exponential operations, using rules for zero and negative exponents, and making calculation errors. Contributing factors included a lack of understanding of basic concepts, a tendency to memorize formulas without grasping their application, and a lack of precision when solving problems. The findings are expected to serve as a basis for evaluating and designing mathematics instruction that places greater emphasis on conceptual understanding.